2008
DOI: 10.1007/s00425-008-0742-0
|View full text |Cite
|
Sign up to set email alerts
|

OsCO3, a CONSTANS-LIKE gene, controls flowering by negatively regulating the expression of FT-like genes under SD conditions in rice

Abstract: The photoperiod is an important environmental stress that determines flowering time. The CONSTANS (CO) and Heading date 1 (Hd1) genes are known to be central integrators of the photoperiod pathway in Arabidopsis and rice, respectively. Although they are both members of the CONSTANS-LIKE (COL) family and have two B-boxes and a CCT domain, rice also possesses novel COL genes that are not found in Arabidopsis. Here, we demonstrate that a novel COL gene, OsCO3, containing a single B-box and a CCT domain, modulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(92 citation statements)
references
References 49 publications
1
90
0
1
Order By: Relevance
“…2. Kim et al (2008) reported that OsB inhibits flowering under SD conditions in rice without the mediation of Hd1 or Ehd1. These data show that HvCO2 and HvCO3 are likely also to be involved in flowering.…”
Section: Qtl Analyses For the Photoperiodic Control Of Flowering In Bmentioning
confidence: 99%
“…2. Kim et al (2008) reported that OsB inhibits flowering under SD conditions in rice without the mediation of Hd1 or Ehd1. These data show that HvCO2 and HvCO3 are likely also to be involved in flowering.…”
Section: Qtl Analyses For the Photoperiodic Control Of Flowering In Bmentioning
confidence: 99%
“…Both of these proteins have a function in induction of flowering, but their regulation pathways are different. Hd1 was demonstrated to promote flowering in short day (SD) (Hayama et al, 2003;Kim et al, 2008). While AtCO promotes flowering in long day (LD) (Putterill et al, 1995;Samach et al, 2000;Zhang et al, 2011).…”
Section: Dccol Protein Sequence Analysismentioning
confidence: 99%
“…Hwaan background) were grown in a growth chamber at 28°C under either short-day (SD) conditions [10/14 h (light/dark)] or long day (LD) conditions [14.5/9.5 h (light/dark)] with light supplied at an intensity of 100 µmol m -2 s -1 , as described in Kim et al 2008. For growth under SD conditions, rice plants were first grown in LD conditions for 20 days and then transferred to SD conditions until flowering.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…For growth under SD conditions, rice plants were first grown in LD conditions for 20 days and then transferred to SD conditions until flowering. The flowering time was measured as the days to heading (DTH), which is the number of days from planting in pots to the emergence of the first panicle from the flag leaf sheath, as described previously (Kim et al 2008). …”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation